Regulation of Candida albicans Interaction with Macrophages through the Activation of HOG Pathway by Genistein - Shuna Cui; Rabeay Y. A. Hassan; Anna Heintz-Buschart; Ursula Bilitewski (Molecules, 2016)
The severity of infections caused by Candida albicans, the most common opportunistic human fungal pathogen, needs rapid and effective antifungal treatments. One of the effective ways is to control the virulence factors of the pathogen. Therefore, the current study examined the effects of genistein, a natural isoflavone present in soybeans, on C. albicans. The genistein-treated C. albicans cells were then exposed to macrophages. Although no inhibition effect on the growth rates of C. albicans was noted an enhancement of the immune response to macrophages has been observed, indicated by phagocytosis and release of cytokines TNF-α and IL-10. The effect of genistein on the enhanced phagocytosis can be mimicked by the fungicides fludioxonil or iprodione, which inhibit the histidine kinase Cos1p and lead to activation of HOG pathway. The western blot results showed a clear phosphorylation of Hog1p in the wild type strain of C. albicans after incubation with genistein. In addition, effects of genistein on the phosphorylation of Hog1p in the histidine kinase mutants Δcos1 and Δsln1 were also observed. Our results thus indicate a new bio-activity of genistein on C. albicans by activation of the HOG pathway of the human pathogen C. albicans.